The role of digitalization in countering corruption and strengthening civil society (Journal of actual problems of jurisprudence, 2020)
Transparency and accountability play a central role in the fight against corruption. The most detrimental effect of corruption is that it undermines faith in government institutions. Information and communication technologies are an invaluable tool, they facilitate the processing, transmission and display of information, are one of the forces that form the twenty-first century. Thanks to fast and cheap communications, ICTs reduce transaction costs and barriers; allow people to seek, acquire and share experiences, ideas, services and technologies at the local, national, regional and international level. Globalization is its most pronounced result. E-government refers to the use of ICTs to improve the provision of services in the public sector, to ensure wider public access to information and to increase government accountability to citizens. It covers the digital interaction between government and citizens, government and business, government and employees, as well as government and local executive bodies. While governments can create open data portals, primarily for economic benefits, civil society can campaign for related activities to include important information about budgets and costs, and can use it to hold governments accountable. We conclude that one of the areas of scientific research consists in the doctrinal development of new phenomena and processes that have arisen and are proceeding in the state-legal sphere under the influence of the digitalization of economics, management and law. Key words. Information law, informatization, anti-corruption, civil society, digital law, digitalization.